2018
DOI: 10.1002/jcp.26417
|View full text |Cite
|
Sign up to set email alerts
|

Beyond cardiomyocyte loss: Role of Notch in cardiac aging

Abstract: The knowledge of the cellular events occurring in the aging heart has dramatically expanded in the last decade and is expected to further grow in years to come. It is now clear that impaired function and loss of cardiomyocytes are major features of cardiac aging, but other events are likewise important. In particular, accumulating experimental evidence highlights the importance of fibroblast and cardiac progenitor cell (CPC) dysfunction. The Notch pathway regulates cardiomyocyte, fibroblast, and CPC activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 131 publications
(162 reference statements)
0
6
0
1
Order By: Relevance
“…It appears that Notch1 activation boosts the function of C-MSCs in the regenerative process. However, Notch1 is altered in aging (Rizzo et al, 2018), which also compromises the function of C-MSCs (Martini et al, 2019). How Notch signaling is affected in the aging heart has not been extensively investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that Notch1 activation boosts the function of C-MSCs in the regenerative process. However, Notch1 is altered in aging (Rizzo et al, 2018), which also compromises the function of C-MSCs (Martini et al, 2019). How Notch signaling is affected in the aging heart has not been extensively investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…A few pathways have been reported in previous studies to determine the stemness of active rapid cycling and dormant stem cells, such as Wnt (Li and Clevers, 2010) and PI3K-Akt (Richmond et al, 2015). Meanwhile, Notch signaling was involved in multiple diseases associated with advanced aging (Sun et al, 2013;Rizzo et al, 2018). Here, we found that Notch activation mimicking by NICD overexpression could restore the neuronal differentiation of Lgr5+ cells in aged OE (Figure 6), while aging weakened capacity to generate progenies from Lgr5+ cells compared with the young OE ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling pathway seems indispensable for functional activities controlling tissue formation in cardiogenesis ( Kratsios et al, 2010 ). Moreover, it is an important cell–cell communication system and its activation after the damage has been demonstrated in several tissues ( Kratsios et al, 2010 ; Rizzo et al, 2017 ). It has been reported that Notch signaling plays a regulatory role in adult cardiac damage and in the cardioprotection preserving cardiac function after ischemia.…”
Section: Discussionmentioning
confidence: 99%